Effect of doping on electrocatalytic dehydrogenation and hydrogenation of methyl decalin-methyl naphthalene system - Verma, Tushar Singh; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2025)
The hydrogen economy can benefit from the use of liquid organic hydrogen carriers (LOHCs) for cross-continent hydrogen transportation in the future. However, dehydrogenation and hydrogenation of hydrogen require catalytic systems. Current research emphasizes selective Pt/Rh doping of Fe, Co, and Ni surfaces as catalysts for the dehydrogenation and hydrogenation of the methyl naphthalene-methyl decalin LOHC system, which has more than 7% hydrogen weight capacity and meets the practical requirements established by the European Union and the United States Department of Energy. Density functional theory-based computational techniques demonstrate how the chemical modification of these surfaces with a Pt and Rh single-atom catalyst (SAC) can improve the efficiency of dehydrogenation and hydrogenation. With a sustainable method, electrochemical dehydrogenation and hydrogenation on these robust surfaces produce effective hydrogen storage for extended periods without losing hydrogen. Furthermore, optimal results for the hydrogenation of 2-methyl naphthalene on Fe-Rh SAC with path-determining step (PDS) = 0.98 eV and dehydrogenation of 1-methyl decalin on Fe-Pt SAC with PDS = 1.49 eV were obtained for the most effective active sites for the enhanced electrochemical process. This study offers new possibilities for the catalytic dehydrogenation and hydrogenation of LOHC systems by highlighting the impact of doping on transition-metal-based catalysts.